2018
DOI: 10.3389/fpls.2018.01503
|View full text |Cite
|
Sign up to set email alerts
|

WHIRLY1 Occupancy Affects Histone Lysine Modification and WRKY53 Transcription in Arabidopsis Developmental Manner

Abstract: Single-stranded DNA-binding proteins (SSBs) are assumed to involve in DNA replication, DNA repairmen, and gene transcription. Here, we provide the direct evidence on the functionality of an Arabidopsis SSB, WHIRLY1, by using loss- or gain-of-function lines. We show that WHIRLY1 binding to the promoter of WRKY53 represses the enrichment of H3K4me3, but enhances the enrichment of H3K9ac at the region contained WHIRLY1-binding sequences and TATA box or the translation start region of WRKY53, coincided with a recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 83 publications
(120 reference statements)
0
33
0
Order By: Relevance
“…This suggests that the accessibility of the chromatin at the WRKY53 promoter region can be driven back and forth, most likely to adjust WRKY53 expression and senescence induction to environmental conditions. Moreover, the single strand-binding protein WHIRLY1 binds to the opened promoter of WRKY53 and represses the enrichment of H3K4me3, but enhances the enrichment of H3K9ac at this gene locus [69]. On top of that, the WRKY53 protein can also directly interact with chromatin modifiers like HISTONE DEACETYLASE9 (HDA9) mediating the recruitment of the POWERDRESS/HDA9 complex to W-box containing promoter regions of key negative senescence regulators.…”
Section: Chromatin Remodeling: Suv2 Powerdress/hda9 Hac1 Jmj16mentioning
confidence: 99%
“…This suggests that the accessibility of the chromatin at the WRKY53 promoter region can be driven back and forth, most likely to adjust WRKY53 expression and senescence induction to environmental conditions. Moreover, the single strand-binding protein WHIRLY1 binds to the opened promoter of WRKY53 and represses the enrichment of H3K4me3, but enhances the enrichment of H3K9ac at this gene locus [69]. On top of that, the WRKY53 protein can also directly interact with chromatin modifiers like HISTONE DEACETYLASE9 (HDA9) mediating the recruitment of the POWERDRESS/HDA9 complex to W-box containing promoter regions of key negative senescence regulators.…”
Section: Chromatin Remodeling: Suv2 Powerdress/hda9 Hac1 Jmj16mentioning
confidence: 99%
“…Alterations in H3K4me3 and H3K9ac globally [54] and specifically at the WRKY53 locus [23,27,55] had been observed during plant senescence. The loss of nuclear isoforms of WHY1 upon exogenous H 2 O 2 treatment prompted us to check whether specific or global histone modification occurred under this condition.…”
Section: H 2 O 2 Induces the Enrichment Of H3k9ac And Rnap II At Wrkymentioning
confidence: 99%
“…The involvement of WHY1 protein in modulating telomere length by binding to the AT-rich region of telomeres has also been suggested [26]. We recently found that Arabidopsis WHY1 accumulation in the nucleus altered the enrichment of di/trimethylation of histone H3 at lysine 4 (H3K4me2/3) and H3K9ac and the recruitment of RNA polymerase II (RNAP II) at the promoter's AT-rich region of WRKY53, repressing WRKY53 transcription [27].…”
Section: Introductionmentioning
confidence: 99%
“…These in silico studies were supported by in vivo evidence with WHIRLY1 being the first protein to be identified in the nucleus and plastids of the same plant cell (Grabowski et al ., 2008); however, its molecular function appears to be compartment‐specific. In the nucleus, WHIRLY1 is associated with WRKY53 promoter and acts as a suppressor of leaf senescence (Miao et al ., 2013; Huang et al ., 2018). In chloroplasts, WHIRLY1 is present in nucleoid fractions where it might be involved in the maintenance of plastid DNA stability (MarĂ©chal et al ., 2009; Krupinska et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%